PENERAPAN STRATEGI MOTIVASI UNTUK MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR NEGERI I GUWOTIRTO SEMESTER I TAHUN PELAJARAN 2017/2018 - Sarniwiati . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
This study aims to determine whether the implementation of the implementation of motivational strategies can improve the performance of teachers SD Negeri I Guwotirto DistrictGiriwoyo Wonogiri District Semester I Lesson Year 2017/2018. This research was conductedwith the design of School Action Research with the subject of the study is the teacher of SDNegeri I Guwotirto Giriwoyo District Wonogiri Regency Semester I Lesson Year 2017/2018.Data collection techniques used observation, interviews, questionnaires, and field notes. Dataanalysis techniques use interpretation model by interpreting the facts obtained for further dataanalysis. The results show that there is an increase in the average value in each cycle. The detailsare from the pre-action stage to the first cycle there is an increase of 0.42, ie from 2.43 to 2.85.Next from cycle I to cycle II there is an increase of 0.51, ie from 2.85 to 3.36. Then the last fromcycle II to cycle III there is an increase of 0.86, ie from 3.36. to 4.22. based on the results ofresearch and supporting theoretical studies, then the conclusion of this study is the application ofmotivation strategies to improve the performance of teachers specifically for elementary schoolteachers.Keywords: Motivational strategy, teacher performance